2022
DOI: 10.1155/2022/3474723
|View full text |Cite
|
Sign up to set email alerts
|

Ficus hirta Vahl. Ameliorates Nonalcoholic Fatty Liver Disease through Regulating Lipid Metabolism and Gut Microbiota

Abstract: Nonalcoholic fatty liver disease (NAFLD) has gradually become one of the most serious liver diseases threatening human health in the world. Currently, Chinese herbal medicine is a potentially important treatment option for NAFLD, and the development of effective Chinese herbal medicine has a good prospect. Previous studies have suggested that Ficus hirta Vahl. (FV) has various protective effects on the liver. In this study, we investigated the therapeutic outcomes of FV treatment for the liver disease and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…This study indicates that dyslipidemia, NAFLD, and obesity were successfully induced in our model by feeding the mice with HFD, which may be due to the significant increase in their energy intake. Our results are in accordance with those reported by previous studies [ 20 , 21 , 26 , 27 , 28 , 29 , 30 , 31 ]. Thus, this model is appropriate for examining the precise mechanisms underlying the anti-dyslipidemic and anti-NAFLD activities of RRBE.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This study indicates that dyslipidemia, NAFLD, and obesity were successfully induced in our model by feeding the mice with HFD, which may be due to the significant increase in their energy intake. Our results are in accordance with those reported by previous studies [ 20 , 21 , 26 , 27 , 28 , 29 , 30 , 31 ]. Thus, this model is appropriate for examining the precise mechanisms underlying the anti-dyslipidemic and anti-NAFLD activities of RRBE.…”
Section: Discussionsupporting
confidence: 94%
“…The abnormal lipid metabolism in the liver and adipose tissue results in hepatic steatosis, typically promoting the secretion of lipids, and hence, contributing to high circulating FFA levels, hypertriglyceridemia, and hypercholesterolemia [ 4 , 6 ]. Consistent with previous reports [ 20 , 21 , 26 , 27 , 28 ], our findings showed that HFD-fed animals presented the typical features of hepatic steatosis and hyperlipidemia, including high serum FFA, hypertriglyceridemia, and hypercholesterolemia, associated with the elevated expression of ATGL in adipose tissue, CD36, LXRα, SREBP-1c, SREBP-2, and HMGCR, as well as decreased CPT1A expression in the liver, which were overall reversed by RRBE treatments, especially at the middle and high doses. Interestingly, although a high-dose RRBE treatment did not reduce serum total-C in HFD-fed mice, it significantly attenuated LDL-C and enhanced HDL-C in the serum, as discussed in more detail below.…”
Section: Discussionsupporting
confidence: 93%
“… Extracts Ficus hirta Vahl. In vivo and in vitro In vivo: 5, 10 mg/kg In vitro: 15, 30mg/mL In vivo: ↓ The mRNA and protein levels of CD36 In vitro: ↓ The mRNA and protein levels of CD36 [ 115 ] Betaine Alkaloids Beta vulgaris In vivo In vivo:1% (w/v) ↓ The mRNA and protein levels of CD36 [ 116 ] Abelmoschus esculentus subfractions Extracts Abelmoschus esculentus In vitro In vitro: 1, 2.5, and 5 µg/mL ↓ The mRNA and protein levels of CD36 [ 118 ] Hydroethanolic extract of Dillenia indica leaf Extracts Dillenia indica leaf In vitro 5, and 10 μg/mL ↓ The protein levels of CD36 [ 120 ] Salvianolic acid B Phenylpropanoids The root of Salvia miltiorrhiza In vivo 10 and 20 mg/kg/d ↓ The mRNA levels of CD36 [ 122 ] Puerarin Flavonoids The root of Pueraria lobata In vivo 0.1% and 0.2% ↓ The mRNA levels of CD36 [ 124 ] Gallic acid Phenols Fruits and nuts In vitro In vitro: 50, 100, and 200 µM ↓ The mRNA and protein levels of CD36 [ 126 ] Theobromine ...…”
Section: Natural Products That Affect the Occurrence And Development ...mentioning
confidence: 99%
“…Quan T et al 115 found that Ficus hirta Vahl . (FV) suppressed the expression and activity of CD36 in HepG2 cell lines induced by palmitate (PA) and mouse model fed with a high-fat diet (HFD), and FV treatment can reverse the exacerbated effects of CD36 on lipid metabolism and inflammation.…”
Section: Natural Products That Affect the Occurrence And Development ...mentioning
confidence: 99%
“…With progress in research, Traditional Chinese Medicine (TCM) and its active ingredients have received widespread attention worldwide because of their potential beneficial effects and special health‐promoting functions, and some of them are preferred in treating T2DM and/or NAFLD (Cai et al, 2021; Li et al, 2022; Quan et al, 2022; Yan et al, 2020). As a medicinal food plant, G. biloba (used as dried leaves of Ginkgo biloba L. from the Ginkgo family) is rich in active ingredients such as flavonoids and terpene lactones, among others, which exhibit significant antioxidant, anti‐hypertensive, anti‐tumor, anti‐inflammatory, significant cardiovascular benefits, and hepatoprotective effects (Adebayo et al, 2022; Fang et al, 2020; Hu et al, 2019; Isah, 2015; Liang et al, 2022; Tao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%